Estimasi Kebutuhan Kalsium Dan Fosfor Ayam Arab Betina Fase Pre-Laying Pada Sistem Pemberian Pakan Bebas Pilih - Aldi Irawan Tarigan; Syafwan; Rasmi Murni (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Arab chickens are descendants of Kriel-Silver Brakel Chickens from Belgium and Indonesian local laying hens. For generations, arab chickens have been delegated as unrivaled arab chickens, because they have a high egg production capacity. This study aimed to calculate the calcium and phosphorus requirements of hens in the pre-laying phase. This study was conducted using a Randomized Block Design (RBD) with 4 groups and each group was repeated 4 times. Each group consists of 9 to 10 birds. The treatments applied were as follows: T1; Control feed, T2; High calcium low phosphorus feed (HCLP) and low calcium high phosphorus feed (LCHP), T3; High calcium high phosphorus (HCHP) feed, high calcium low phosphorus feed (HCLP) and low calcium high phosphorus feed (LCHP). P4: Control feed, high calcium high phosphorus (HCHP) feed, high calcium low phosphorus feed (HCLP), and low calcium high phosphorus (HCLP) diet. The observed variables were feed consumption, calcium and phosphorus consumption and calcium and phosphorus concentrations. The data obtained were analyzed using variance (ANOVA) and if the treatments had a significant effect, it was continued with the Duncan Multiple Range Test. The results showed that the treatments had a significant effect on all observed variables, namely feed consumption, calcium consumption, phosphorus consumption, calcium concentration and phosphorus concentration (P<0.05). It was concluded that the concentration of Ca (2.91-2, 97%) and P (0.51-0.52%) of the feed consumed by Arabic hens with free-choice feeding method in the pre-laying phase were higher than the concentration of Ca (2.70%) and concentration of phosphorus (0.48%) used in the standard Hy-line phase brown chicken pre-laying phase.